ESTUDIO DEL CONSUMO ENERGÉTICO EN LAS VIVIENDAS DE LA CIUDADELA MUÑOZ RUBIO, DE LA CIUDAD DE BABAHOYO, PROVINCIA DE LOS RÍOS - BERMÚDEZ CEVALLOS, GARY ALEXANDER (2018)
The industrial development and the demographic explosion worldwide have caused a disproportionate increase in the consumption of electrical energy, which has as an immediate consequence the greenhouse effect that, according to Muñoz and Bazán (2005), have: "... possible impact on the issues of climate change and possible mitigation actions that can be taken to reduce the amount of emissions and, therefore, possible changes in climate. ", being direct sources of emissions: industries, residences, businesses, public services and energy transformation. Taking into account the implicit risk, this study focuses on the analysis of energy consumption in the dwellings of the Muñoz Rubio Citadel in the city of Babahoyo, Province of Los Ríos, in order to investigate its impact, make it known to the community of the Muñoz Rubio Citadel and propose educational solutions to achieve citizen cooperation in order to reduce the consumption of electricity. To collect the information, the observation technique was used and a questionnaire was applied to an intentional sample of 16 clients of the National Electricity Corporation (CNEL), selecting the community of the Muñoz Rubio Citadel in the city of Babahoyo as the observation unit. , Province of the Rivers. For the fulfillment of this purpose, the objective has been to study the energy consumption in the dwellings of the Muñoz Rubio Citadel in the city of Babahoyo, Province of Los Ríos, which will conceptualize energy consumption and its impact on the Ciudadela Muñoz Rubio community of the city of Babahoyo, Province of Los Ríos, and get to know the opinion of the community to define some awareness strategies that help to minimize electricity consumption.